(untitled) (Per Musi, 2001)
In this presentation I shall propose that music is a form of discourse. This has three fundamental principles for music teachers and these principles present some implications for teaching methods and curriculum structure. I use the word ’discourse’ in an everyday, non-technical sense. Associated terms include ’argument’, ’interchange of ideas’, ’conversation’, ’expression of thought’ and, most important, ’symbolic form’. Discourse manifests itself in a variety of ways, not only through words. I wish to argue that music is part of a web of human discourse, rather than some curious activity separated from life in general. I shall also argue that music is not object but always contemporary event. Musical processes have a degree of cultural autonomy with multiple interpretations, uses and responses.